MODERN CYBERNETIC TERRORISM AND HIS SOCIAL CONSEQUENCES - N. Grigoriev; E. Rodyukov (Вестник университета, 2019)
The article is devoted to the study of the theoretical foundations of modern cyber terrorism. Given that policy now covers all spheres of public life and, therefore, increasing the problem of information security of society in General and each person in particular. Along with terrorism on a global scale in relation to processes of globalization and integration in the society is coming and a change in the threats, particularly the threat of cyber terrorism.